Federal Taxation: 1986 Edition/Individual Taxation: 1986 Edition (Book). - Fortin, Karen A.; Hendrickson, Harvey S. (The Accounting Review, 1986)
Abstract Reviews two books "Federal Taxation: 1986 Edition," and "Individual Taxation: 1986 Edition," edited by James W. Pratt, Jane O. Burns and William N. Kulsrud.